Orbital control on the thermocline structure during the past 568 kyr in the Solomon Sea, southwest equatorial Pacific. (1st November 2022) - Lo, Li; Shen, Chuan-Chou; Zeeden, Christian; Tsai, Yi-Hsueh; Yin, Qiuzhen; Yang, Chun-Chih; Chang, Tzu-Ling; Su, Yu-Chu; Mii, Horng-Sheng; Chuang, Chih-Kai; Chen, Yi-Chi
Abstract: The Solomon Sea is the main source of the equatorial undercurrent and the main crossroad of the equatorial region and the South Pacific Ocean. Based on multi-species planktonic foraminiferal geochemical proxies, here we reconstruct the vertical thermal-hydrological variabilities over the last 568, 000 years in the Solomon Sea. The proxies used include the differences between δ 18 O data of the surface dweller Globigerinoides ruber (white ) and the subsurface dweller Pulleniatina obliquiloculata (Δδ 18 Oc ), the sea surface temperature (SST) and the upper thermocline temperature (UTT) as well as their differences (ΔT), and the seawater oxygen isotope differences (Δδ 18 Ow ). Both the SST and UTT records feature similar timing of warming, which is 2–4 kyr earlier than the G/IG boundaries for the past six terminations. Different from the other five terminations, both SST and UTT records of Termination V show a persistent and early increase of 5–7 °C in 10 kyr since ∼440 ka. On the obliquity band, higher SST and UTT correspond to larger obliquity, suggesting higher subtropical South Pacific input. This argument is supported by lower ΔT and higher Δδ 18 Ow . In the meantime, higher SST and UTT also correspond to precession minimum, suggesting an expansion of the mixed layer with lower ΔT and greater Δδ 18 Ow . Our results show complex interactions between precipitation-evaporation and water masses exchange in the Solomon Sea. The clear obliquity signal observed in multiple proxies reveals strong interactions between the Solomon Sea and the mid-high latitude South Pacific regions. Highlights: High resolution surface and subsurface reconstructions in the south marginal warm pool region during the past 568, 000 years Strong precession and obliquity pacings suggest complex atmospheric and oceanic processes in the Solomon Sea. Termination V in Solomon Sea shows very early and persistent warming, induced by both insolation and CO2 forcings.